PERSEPSI MASYARAKAT TERHADAP DAMPAK SOSIAL EKONOMI DARI PERUSAHAAN PERKEBUNAN KELAPA SAWIT PT. HENRISON INTI PERSADA KABUPATEN SORONG PAPUA BARAT - Jakson Arnold Klasibin; Caroline B. D. Pakasi; Celcius ., Talumingan (AGRI-SOSIOEKONOMI, 2018)
This study aims to determine the public perception of the socio-economic impact of oil palm plantation company PT. Henrison Inti Persada in Sorong district of West Papua. This research was conducted from February to April 2017. The data used are primary data and secondary data. This research was conducted with in-depth interview technique with 30 (thirty) respondents in this case the people living around this company operate and also use observation and literature study. The data obtained will be analyzed using descriptive analysis which each answer is tested and tested using Likert scale. The results of this study indicate that the index of public perceptions on the socio-economic impact of oil palm plantation companies PT. Henrison Inti Persada is at 81.11% and is relatively high, meaning the existence of oil palm plantation company PT. Henrison Inti Persada has a social and economic impact that must be increased again to the community, because every indicator has a positive impact as well as the negative impact that must be viewed by the oil palm plantation company PT. Henrison Inti Persada.